The Effect of Using Living Motor Model In Learning Freestyle Swimming - Salahaddin, Mustafa (Journal of Physical Education, 2009)
The aim of the research is to identify the effect of using and imitating a living motor model in learning freestyle movements as well as identifying the differences among experimental group that used this model and the controlling group that did not use it. the researcher used the experimental method. It includes the positive effect of using and imitating a living motor model in learning the movements of freestyle in swimming. There are significant statistical differences between the controlling and the experimental groups in the results of the test used. The researcher used freestyle swimming tests taken from his MA thesis. The subjects were (24) students from the college of physical education/university of Baghdad who do not know how to swim. They were divided into two equal groups; controlling group 12 students and experimental group 12 students. The researcher concluded that using a living motor model has a positive effect in learning freestyle swimming and the immediate outside corrections has a positive effect on learning freestyle swimming movements. The researcher recommended using this living motor model for teaching freestyle swimming movements. In addition to that, he recommended the necessity of displaying and applying different movements of freestyle swimming and mastering them on land before entering into water. This will help the learner to perceive the movement correctly and as well as having clear mental imagery about performing it. Finally, he recommended the necessity of immediate correction of mistakes and helping the learner to compare between the wrong performance and the correct performance demonstrated by a live model